Environmental Governance Meets Reality: A Micro-Scale Perspective on Sustainability Certification Schemes for Oil Palm Smallholders in Jambi, Sumatra. Issue 5 (3rd May 2020) - Martens, Katrin; Kunz, Yvonne; Rosyani, Ir.; Faust, Heiko
Abstract: Multi-stakeholder sustainability certification schemes have become a favorite instrument for applying good governance, though studies indicate their inefficiency at the producer level. In this study, we used a mixed-method approach to first, map the institutional context of independent oil-palm smallholders in rural Sumatra while, second, reflecting upon the impact of the Smallholder Standard proposed by the Roundtable on Sustainable Palm Oil on smallholder management practices. We hold that non-recognition of micro-scale perspectives within governance processes may partially explain noncompliance with certification principles among smallholders. The Smallholder Standard appears unable to mitigate challenges important for smallholders, who in turn cannot properly comply with it, due to problems including weather instability and high management costs. We suggest that certification schemes need to work on some overlooked but essential preconditions of good governance, namely gaining micro-level visibility and acceptance.